Fiery Cell Death: Pyroptosis in the Central Nervous System. Issue 1 (January 2020) - McKenzie, Brienne A.; Dixit, Vishva M.; Power, Christopher
Abstract : Pyroptosis ('fiery death') is an inflammatory type of regulated cell death (RCD), which occurs downstream of inflammasome activation. Pyroptosis is mediated directly by the recently identified family of pore-forming proteins known as gasdermins, the best characterized of which is gasdermin D (GSDMD). Recent investigations implicate pyroptosis in the pathogenesis of multiple neurological diseases. In this review, we discuss molecular mechanisms that drive pyroptosis, evidence for pyroptosis within the CNS, and emerging therapeutic strategies for its inhibition in the context of neurological disease. Highlights: Pyroptosis ('fiery death') is a lytic and highly inflammatory regulated cell death program, recently found to be driven by members of the gasdermin family, most notably gasdermin D (GSDMD). GSDMD is a pore-forming executioner protein that is proteolytically cleaved and activated by proinflammatory caspases (caspase-1/4/5/11). These caspases are localized on inflammasomes, large cytosolic protein complexes that serve as platforms upon which activated proinflammatory caspases cleave and activate their protein substrates. Cleaved GSDMD oligomerizes and forms pores in the plasma membrane, leading to disruption of local osmotic potential, formation of pyroptotic bodies, and eventual membrane rupture. During neuroinflammation and neurodegeneration, inflammasome activation and pyroptosis are initiated by acute perturbations in homeostasis (e.g., mitochondrial dysfunction, ion flux) as well as danger signals in the microenvironment (e.g., extracellular ATP, aberrant protein aggregates, double-stranded DNA, microbial molecules) that are present in the injured or diseased CNS. Pyroptosis occurs in multiple CNS cell types under pathological conditions (e.g., multiple sclerosis, Alzheimer's disease, and stroke), leading to both neuroinflammation and neurodegeneration through multiple mechanisms. Targeting pyroptosis therapeutically shows promise in multiple preclinical models of neurological injury and disease.